Influence of Patient Size and Photon Energies on IMRT Plans for Localized Prostate Cancer - Mohammed, Khabat A.; Faraj, Kharman A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
The localized prostate cancer treatment with intensitymodulated radiation therapy (IMRT) produces precise radiation doses that protect healthy tissues but continues to generate toxicity in the bladder and rectum. Our study aims to evaluate how patient size and photon energy influence IMRT plan quality in localized prostate cancer. Patients with localized prostate cancer (n = 20) received IMRT treatment in a retrospective analysis through two groups (small n = 12 and large n = 8) based on planning target volume isocenter diameter measurements. The same planning objectives guided the build of 6 MV and 10 MV photon plans for each patient. The assessment included monitor units (MUs) as well as examination of homogeneity index and conformity index, and dose–volume histogram metrics when comparing different energies and patient size groups. The target coverage and dose uniformity between 6 MV and 10 MV were equivalent, but 10 MV plans cut down MUs by 6.6% in a small group. The size of patients played a stronger influence on organs at risk (OAR) than energy utilization during treatment planning. Large patients received 22% lower mean bladder doses, 30% lower bladder V10–V50 values, and 3396% (6 MV) less V20–V50 doses in the left femoral head compared to smaller patients. The size of the patient influenced OAR sparing more than the selection of photon energy, which had limited and size‐dependent effects. Therefore, patient size has to be considered in energy choice, treatment planning, and clinical trial design to individualize treatment and minimize toxicity.